Vitamin D Status Among Children With Juvenile Idiopathic Arthritis: A Multicenter Prospective, Non-randomized, Comparative Study - Kondratyeva, Elena I.; Odinaeva, Nuriniso D.; Klimov, Leonid Ya; Podchernyaeva, Nadeshda S.; Ilenkova, Natalya I.; Dolbnya, Svetlana V.; Zhekaite, Elena K.; Kuryaninova, Victoria A.; Kotova, Yuliya V.; Tikhaya, Margarita I.; Shitkovskaya, Elena P.; Bychina, Liubov V.; et al. (Frontiers in Pediatrics, 2022)
Background: Juvenile idiopathic arthritis (JIA) is a chronic autoimmune disease characterized by destructive and inflammatory damage to the joints. The aim in this study was to compare vitamin D levels between children and adolescents, 1-18 years of age, with juvenile idiopathic arthritis (JIA) and a health control group of peers. We considered effects of endogenous, exogenous, and genetic factors on measured differences in vitamin D levels among children with JIA. Methods: Our findings are based on a study sample of 150 patients with various variants of JIA and 277 healthy children. The blood level of vitamin D was assessed by calcidiol (25(OH)D). The comprehensive study included an assessment age and sex; level of insolation in three regions of country (centr, south, north); assessment of dietary intake of vitamin D; effect of prophylactic doses of cholecalciferol; a relationship between the TaqI, FokI, and BsmI polymorphisms of the VDR gene and serum 25(OH)D concentration. Results: We identified a high frequency of low vitamin D among children with JIA, prevalence of 66%, with the medial level of vitamin D being within the range of ‘insufficient’ vitamin D. We also show that the dietary intake of vitamin D by children with JIA is well below expected norms, and that prophylactic doses of vitamin D supplementation (cholecalciferol) at a dose of 500-1000 IU/day and 1500-2000 IU/day do not meet the vitamin D needs of children with JIA. Of importance, we show that vitamin D levels among children with JIA are not affected by clinical therapies to manage the disease nor by the present of VDR genetic variants. Conclusion: Prophylactic administration of cholecalciferol and season of year play a determining roles in the development of vitamin D deficiency and insufficiency.